DAGmaps: Space Filling Visualization of Directed Acyclic Graphs - Tsiaras, Vassilis; Triantafilou, Sofia; Tollis, Ioannis (Journal of Graph Algorithms and Applications, 2009)
Gene Ontology information related to the biological role of genes is organized in a hierarchical manner that can be represented by a directed acyclic graph (DAG). Space filling visualizations, such as the treemaps, have the capacity to display thousands of items legibly in limited space via a two-dimensional rectangular map. Treemaps have been used to visualize the Gene Ontology by first transforming the DAG into a tree. However this transformation has several undesirable effects such as producing trees with a large number of nodes and scattering the rectangles associated with the duplicates of a node around the display rectangle. In this paper we introduce the problem of visualizing a DAG with space filling techniques without converting it to a tree first, we present two special cases of the problem, and we discuss complexity issues. <!—->